Fe(IV) alkylidenes via protonation of Fe(II) vinyl chelates and a comparative Mossbauer spectroscopic study - Lindley, Brian M.; Swidan, Ala'Aeddeen; Lobkovsky, Emil B.; Wolczanski, Peter T.; Adelhardt, Mario; Sutter, Jörg; Meyer, Karsten (Chemical Science, 2015)
Treatment of cis-Me2Fe(PMe3)(4) with di-1,2-(E-2-(pyridin-2-yl)vinyl)benzene ((bdvp)H-2), a tetradentate ligand precursor, afforded (bdvp)Fe(PMe3)(2) (1-PMe3) and 2 equiv. CH4, via C-H bond activation. Similar treatments with tridentate ligand precursors PhCH=NCH2(E-CH=CHPh) ((pipp)H-2) and PhCH=N(2-CCMe-Ph) ((pipa)H) under dinitrogen provided trans-(pipp)Fe(PMe3)(2)N-2 (2) and trans-(pipvd) Fe(PMe3)(2)N-2 (3), respectively; the latter via one C-H bond activation, and a subsequent insertion of the alkyne into the remaining Fe-Me bond. All three Fe(II) vinyl species were protonated with H[BAr4F] to form the corresponding Fe(IV) alkylidene cations, [(bavp)Fe(PMe3)(2)][BAr4F] (4-PMe3), [(piap)Fe(PMe3)(3)]-[BAr4F] (5), and [(pipad) Fe(PMe3)(3)][BAr4F] (6). Mossbauer spectroscopic measurements on the formally Fe(II) and Fe(IV) derivatives revealed isomer shifts within 0.1 mm s(-1), reflecting the similarity in their bond distance